2010
DOI: 10.1111/j.1462-2920.2010.02187.x
|View full text |Cite
|
Sign up to set email alerts
|

Herbaspirillum seropedicae rfbB and rfbC genes are required for maize colonization

Abstract: SummaryIn this study we disrupted two Herbaspirillum seropedicae genes, rfbB and rfbC, responsible for rhamnose biosynthesis and its incoporation into LPS. GC-MS analysis of the H. seropedicae wild-type strain LPS oligosaccharide chain showed that rhamnose, glucose and N-acetyl glucosamine are the predominant monosaccharides, whereas rhamnose and N-acetyl glucosamine were not found in the rfbB and rfbC strains. The electrophoretic pattern of the mutants LPS was drastically altered when compared with the wild t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(94 citation statements)
references
References 57 publications
4
85
0
Order By: Relevance
“…In a Tn5 mutant of A. brasilense affected in the biosynthesis ofd TDP-rhamnose, LPS composition was modified and resulted in impaired attachment of the mutant to maize roots and reduced root colonization [29]. Additional studies recently were undertaken on H. serepedicae by Balsanelli et al [30] confirmed these data. In addition to LPS, a major outer membraneprotein from A. brasilense strain Cd was purified and shown, by in vitro adhesion assays, to bind to roots of wheat, corn and sorghum seedlings [31].…”
Section: Colonization Of Rice Roots By P Stutzeri A1501supporting
confidence: 69%
“…In a Tn5 mutant of A. brasilense affected in the biosynthesis ofd TDP-rhamnose, LPS composition was modified and resulted in impaired attachment of the mutant to maize roots and reduced root colonization [29]. Additional studies recently were undertaken on H. serepedicae by Balsanelli et al [30] confirmed these data. In addition to LPS, a major outer membraneprotein from A. brasilense strain Cd was purified and shown, by in vitro adhesion assays, to bind to roots of wheat, corn and sorghum seedlings [31].…”
Section: Colonization Of Rice Roots By P Stutzeri A1501supporting
confidence: 69%
“…1B). Previously, Balsanelli et al (3) showed that strains unable to synthesize LPS were severely impaired in maize colonization. These authors also showed that the rmlB gene, whose product is involved in LPS biosynthesis, was upregulated by naringenin (4-fold), in agreement with our results showing that naringenin can modulate genes involved in the biosynthesis and modification of LPS.…”
Section: Vol 77 2011 Naringenin-regulated Genes Of Herbaspirillum Smentioning
confidence: 99%
“…To check whether any of the mutations influenced the colonization of maize (Zea mays), the protocol of Balsanelli et al (3) was used to test bacterial cell adhesion to root surface and internal colonization. No difference was observed between the parental strain (SmR1) and mutants in growth and root surface attachment (data not shown).…”
Section: Vol 77 2011 Naringenin-regulated Genes Of Herbaspirillum Smentioning
confidence: 99%
“…Mutational analyses suggest that surface characteristics of bacteria play an important role in the establishment of endophytes in roots. The lipopolysaccharide composition, particularly the rhamnose content had an impact on attachment to and endophytic colonization of maize roots by H. seropedicae [30]. In a study conducted on rice plant it was found that exopolysaccharide production is necessary for plant colonization by the nitrogen-Fixing endophyte Gluconacetobacter diazotrophicus [31].…”
Section: Introductionmentioning
confidence: 99%